(untitled) (Bangladesh Journal of Otorhinolaryngology, 2019)
Objective: To find out the incidence of malignancy in patient with solitary thyroid nodule. Methods: This cross-sectional study was carried out with 100 solitary thyroid nodular patients who admitted in Otolaryngology & Head-Neck Surgery Department of Sir Salimullah Medical College Mitford Hospital (SSMCMH) & Bangabondhu Sheikh Mujib Medical Univercity (BSMMU), Dhaka, from July 2012 to December 2013, where all patients were admitted throughout patient department. All patients were selected as per described criteria from the Department of Otolaryngology & Head-NeckSurgery,SSMCMH & BSMMU.Diagnosed the cases by detail history,clinical examination,investigations,analysed data presented by various tables,figures. Results: In this study mean age of the patients of solitary thyroid nodule was 35.613.54 years and the highest frequency (38%) was within 21-30 years of age with female predominance(78%).Thyroid swelling was the common presentation in all9100%) cases, some patients also presented with other symptoms like cervical lymphadenopathy 13(13%) cases, dysphagia 1(1%), dyspnoea 1(1%), hoarseness of voice 1(1%) case & no bone metastetic found.In this series of solitary thyroid nodules constituted 73% firm, 6% hard and 11% cystic. Malignancy was found more in firm nodule 13(72.22%).Isotopes scanning of the thyroid gland were done to see the functional status of the nodule. We found most 96(96%) of the nodules were cold & 4(4%) were warm nodule & no hot nodule found. In our study out of 96 cold nodular goiters we found 18(18.75 %) malignant & no malignant case found from rest of 4 warm cases. In our study, out of 89 solid nodule 72(80.89%) were benign & 17(19.10%) nodule were malignant and out of 11 cystic nodule 10(90.9%) were benign & 1 (9.1%) was malignant. In this study, most of the benign & malignant nodules were predominantly solid. Study showed the malignancy is significantly (p<0.001) more in solid than cystic solitary thyroid nodule. Final diagnosis in this study was on the basis of histopathological reports record. Out of 100 cases, 54 cases (54%) were proven as nodular goitre & 2 % were thyroiditis in non-neoplastic lesion & in neoplastic lesion we found 26(26%) Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 105-114